Landforms of high mountains - Stahr, Alexander; Langenscheidt, Ewald (Springer Berlin Heidelberg Imprint: Springer, 2015)
This image atlas and reference book is written in simple language that can be understood by a broad audience. The work comprehensively explains the geomorphological forms of high mountains using many examples like glacial erosion forms and deposits such as moraines and gravel terraces, which are illustrated with numerous photographs. Landslide landscapes, volcanoes, weathering, and erosion are other examples discussed. These examples are from across the world, including the Himalayas, the Alps, the Andes, and the Southern Alps of New Zealand. This work is useful for laymen who are interested in geosciences, especially high-mountain landforms, as well as for students and teachers of earth sciences.